The use of participatory action research to improve energy intake of the soccer athletes - Irwan Budiono; Arif Setiawan; Arif Rahmat Kurnia (Program Studi Ilmu Keolahragaan Program Pascasarjana Universitas Negeri Yogyakarta, 2021)
It was estimated that 5, 3 % of Universitas Negeri Semarang (UNNES) soccer athletes were malnourished. The consumption survey results show that the average dietary energy intake (DEI) was 63.24% of the dietary reference intake (DRI). The purpose of this study was to improve the energy intake of athletes. This research was using a participatory action research method. The study was divided into 2 cycles which allocated in 30 days. This research was using a total sampling method. A total of 19 UNNES soccer athletes were involved as research subjects. Data on nutritional status and energy intake were analyzed to evaluate the success of participatory action research. Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ) used to take dietary energy intake data, Nutrition status measured by BMI using Seca scales and microtome. A non-parametric test was used to analyze the success of the participatory action research program. Results showed that participatory action research can improve energy intake (EI) in athletes. Baseline data showed that the average percentage of DEI was 63.24% from the DRI. The average percentage of DEI increased became 71.38% at the end of the first cycle and rose into a 91.91 % at the end of the second cycle. It is recommended for trainers to include nutrition assistance activities as part of the exercise program for athletes.